Killing Us Quietly - Vernon, Irene S. (2025)
Over the past five centuries, waves of diseases have ravaged and sometimes annihilated Native American communities. The latest of these silent killers is HIV/AIDS. The first book to detail the devastating impact of the disease on Native Americans, Killing Us Quietly fully and minutely examines the epidemic and its social and cultural consequences among three groups in three geographical areas. Through a series of personal narratives, the book also vividly conveys the terrible individual and emotional toll the disease is taking on Native lives. Exploring Native urban, reservation, and rural perspectives, as well as the viewpoints of Native youth, women, gay or bisexual men, this study combines statistics, Native demography and histories, and profiles of Native organizations to provide a broad understanding of HIV/AIDS among Native Americans. The book confronts the unique economic and political circumstances and cultural practices that can encourage the spread of the disease in Native settings. And perhaps most important, it discusses prevention strategies and educational resources. A much-needed overview of a national calamity, Killing Us Quietly is an essential resource for Natives and non-Natives alike.